Evaluation of hidden hearing loss in normal-hearing firearm users - Grinn, Sarah K.; Le Prell, Colleen G. (Frontiers in Neuroscience, 2022)
Some noise exposures resulting in temporary threshold shift (TTS) result in cochlear synaptopathy. The purpose of this retrospective study was to evaluate a human population that might be at-risk for noise-induced cochlear synaptopathy (i.e. “hidden hearing loss”). Participants were firearm users who were 1) at-risk for prior audiometric noise-induced threshold shifts, given their history of firearm use, 2) likely to have experienced complete threshold recovery if any prior TTS had occurred, based on this study’s normal-hearing inclusion criteria, and 3) not at risk for significant age-related synaptopathic loss, based on this study’s young-adult inclusion criteria. 70 participants (age 18-25 yr) were enrolled, including 33 firearm users (EXP), and 37 non-firearm users (CNTRL). All participants were required to exhibit audiometric thresholds <20 dB HL bilaterally, from .25 - 8 kHz. The study was designed to test the hypothesis that EXP participants would exhibit a reduced cochlear nerve response compared to CNTRL participants, despite normal-hearing sensitivity in both groups. No statistically significant group differences in auditory performance were detected between the CNTRL and EXP participants on standard audiometry, extended high-frequency audiometry, Words-in-Noise performance, distortion product otoacoustic emission, middle ear muscle reflex, or auditory brainstem response. Importantly, 91% of EXP participants reported that they wore hearing protection either “all the time” or “almost all the time” while using firearms. The data suggest that consistent use of hearing protection during firearm use can effectively protect cochlear and neural measures of auditory function, including suprathreshold responses. The current results do not exclude the possibility that neural pathology may be evident in firearm users with less consistent hearing protection use. However, firearm users with less consistent hearing protection use are also more likely to exhibit threshold elevation, among other cochlear deficits, thereby confounding the isolation of any potentially selective neural deficits. Taken together, it seems most likely that firearm users who consistently and correctly use hearing protection will exhibit preserved measures of cochlear and neural function, while firearm users who inconsistently and incorrectly use hearing protection are most likely to exhibit cochlear injury, rather than evidence of selective neural injury in the absence of cochlear injury.